(untitled) - Heady, Earl O. (New Jersey, 1954)
The aim of this subject is for students of agricultural science and agricultural economics to understand the principles of management economics applied to the operation of agricultural business; to understand decision analysis under risk and uncertainty; to be able to model and analyse agricultural systems; to be able to analyse agricultural investment and evaluate the profitability and sources, and business risk and financial risk of alternative resource uses in agricultural businesses; evaluate business growth strategies; and understand agricultural price risk management strategies.
Keywords: Farm management,Quản lý trang trại